Distributions of oxytocin and vasopressin 1a receptors in the Taiwan vole and their role in social monogamy. (1st March 2016) - Chappell, A. R.; Freeman, S. M.; Lin, Y. K.; LaPrairie, J. L.; Inoue, K.; Young, L. J.; Hayes, L. D.
Abstract: Social monogamy is a mating strategy rarely employed by mammalian species. Laboratory studies in socially monogamous prairie voles Microtus ochrogaster demonstrate that oxytocin and vasopressin act within the mesolimbic dopamine pathway to facilitate pair‐bond formation. Species differences in oxytocin receptor (OTR) and vasopressin 1a receptor (V1aR) distribution in this pathway are associated with species differences in mating strategy. Here, we characterize the neuroanatomical distribution of OTR and V1aR binding sites in naturally occurring populations of Taiwan voles Microtus kikuchii, which purportedly display social monogamy. Live trapping was conducted at two sites in 2009‐2010 and receptor autoradiography for OTR and V1aR was performed on brains from 24 animals. OTR binding in two brain regions where OTR signaling regulates pair‐bonding were directly compared with that of prairie voles. Our results show that like prairie voles, Taiwan voles exhibit OTR in the prefrontal cortex, insular cortex, claustrum, nucleus accumbens, caudate‐putamen, dorsal lateral septal nucleus, central amygdala and ventromedial hypothalamus. Unlike prairie voles, Taiwan voles exhibit OTR binding in the CA3 field of the hippocampus, as well as the indusium griseum, which has only previously been documented in tuco‐tucos Ctenomys haigi, Ctenomys sociabilis, Syrian hamsters Mesocricetus auratus and naked mole‐rats Heterocephalus glaber . V1aR binding was present in the ventral pallidum, lateral septum, nucleus basalis, bed nucleus of the stria terminalis, hippocampus, medial amygdala, and anterior, ventromedial and dorsomedial hypothalamus. Marked individual differences in V1aR binding were noted in the cingulate cortex and several thalamic nuclei, remarkably similar to prairie voles. While pharmacological studies are needed to determine whether oxytocin and vasopressin are involved in pair‐bond formation in this species, our results lay a foundation for future investigations into the role of these neuropeptides in Taiwan vole social behavior. Abstract : Neuroanatomical distributions of oxytocin receptor (OTR) and vasopressin 1a receptor (V1aR) binding sites were characterized in naturally occurring populations of Taiwan voles Microtus kikuchii, which allegedly display social monogamy. We live‐trapped at two sites in 2009–2010 and preformed receptor autoradiography for OTR and V1aR on brains from 24 animals. OTR binding in two brain regions where OTR signaling regulates pair‐bonding were directly compared with that of prairie voles Microtus ochrogaster, the model organism for social monogamy. We found several similarities between Taiwan voles and prairie voles in OTR binding, supporting the hypothesis that Taiwan voles are socially monogamous.